Digital Marketing Produk Usaha Mikro, Kecil, dan Menengah Lurik Mozaik - Nurjanah, Adhianty; Prawoto, Nano; Iswanto, Iswanto (Universitas Muhammadiyah Yogyakarta, 2022)
During COVID-19, the micro, small and medium enterprise (MSME) sector was the most affected. Many MSMEs went out of business due to failing to adapt to these conditions. MSME Batik Lurik Mozaik Sumberadi Sleman Yogyakarta is one of the MSMEs affected and needs digital marketing assistance in marketing. This service method is carried out through several stages. The preparation stage was conducted through observations, interviews, and focus group discussions (FGD) to get an initial assessment. After that, the implementation, monitoring and feedback stages were also held. This service program has succeeded in increasing the knowledge of Lurik Mozaik MSME managers regarding digital marketing and repackaging by 85%. The implication is that MSME Batik Lurik Mozaik Sumberadi Sleman can expand its marketing network and focus on developing digital-based marketing quality.Â